Chirality Induction by Formation of Assembled Structures Based on Anion‐Responsive π‐Conjugated Molecules. Issue 48 (21st October 2013) - Maeda, Hiromitsu; Hane, Wataru; Bando, Yuya; Terashima, Yoshitaka; Haketa, Yohei; Shibaguchi, Hiroshi; Kawai, Tsuyoshi; Naito , Masanobu; Takaishi , Kazuto; Uchiyama , Masanobu; Muranaka , Atsuya
Abstract Anion‐responsive π‐conjugated compounds having chiral alkyl chains were synthesized. Circular dichroism (CD) and circularly polarized luminescence (CPL) were observed in the solution‐state assemblies of the chiral anion receptors and those of their anion complexes as salts of a planar triazatriangulenium cation. The CD and CPL spectral patterns of the ion‐pair‐based assemblies were completely opposite to those of the anion‐free assemblies, and this suggests that anion binding and subsequent ion pairing change the chirality of the assembly modes.